Retraction Note to: Vitamin A deficiency and sleep disturbances related to autism symptoms in children with autism spectrum disorder: a cross-sectional study - Jing Wen; Ting Yang; Jiang Zhu; Min Guo; Xi Lai; Ting Tang; Li Chen; Jie Chen; Ming Xue; Tingyu Li (BMC, 2021)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12887-021-03000-8.